A linear and large-range pressure sensor based on a graphene/silver nanowires nanobiocomposites network and a hierarchical structural sponge. (8th February 2018) - Dong, Xuchu; Wei, Yong; Chen, Song; Lin, Yong; Liu, Lan; Li, Jing
Abstract: It is challenging to manufacture pressure-sensing materials that possess linearly sensitive regime, high sensitivity, and large-range detection for the development of artificial intelligence products. Herein, a very simple approach is proposed to fabricate piezoresistive sensors based on hierarchical structure sea sponges and composites conductive networks of polydopamine reduced graphene oxides and silver nanowires. The hierarchical structures of porous sea sponges including the contacting of multi-scale porous skeletons and the bending of nodes vary synchronously, resulting in the linear relationship between applied compress strain and resistances, Moreover, the as-prepared pressure sensor exhibits a high sensitivity (S = 0.016 kPa −1 at 0-40 kPa) and a large area detection range (gauge factor = 1.5 at 0-60% strain). The synergetic effect of the composites conductive network endows the sensor with excellent reproducibility (>7000 loading/unloading cycles) and fast response time (<54 ms). In addition, demonstrate various applications of pressure sensor for health monitoring ranging from human leg to foot activities (such as toes on points, Restless Legs Syndrome (RLS) and walking).